Earnings quality and cost of debt: evidence from Portuguese private companies. Issue 2 (3rd October 2016) - Carmo, Cecília Rendeiro; Moreira, José António Cardoso; Miranda, Maria Cristina Souto
Abstract : Purpose: The purpose of this paper is to test the relationship between earnings quality and the cost of debt for private companies in a "code-law" country (Ball et al., 2000). The analysis controls for company size, debt level and audited information. Design/methodology/approach: The paper uses the ordinary least squares regression technique to test the relationship between earnings quality and the cost of debt. Findings: The collected empirical evidence shows a negative relationship between earnings quality and the cost of debt and controls for company size and debt level. Such a relationship is stronger when the company information is audited. Research limitations/implications: Similar to other studies, this paper has two main limitations. There was no access to specific data on the interest rates charged on bank loans, implying that the cost of debt is measured by the ratio of the interest expense to interest-bearing debt. The research only uses earnings quality measures based on abnormal accruals. Practical implications: The collected evidence suggests that earnings quality have economic consequences for private companies by affecting their cost of debt, similar to those observed in previous studies for listed companies. This evidence can be seen as an incentive for private companies to increase their financial information quality. For debt providers, namely, financial institutions, the findings can be of interest to help them price properly the loans they make available to private companies. In general, the findings of this research can be of interest for company managers and financial institutions in countries with an institutional environment similar to that of Portugal. Originality/value: The relation between earnings quality and the cost of debt has been so far studied for listed companies in "common law" countries. This paper provides new and complementary evidence about such relation for private companies and "code-law" country.